Analysis of the Properties of Recycled Aggregates for Unbound Granular Asphalt Pavement Layers - Freire, A. C. (2010)
The main purpose of this paper is to analyse the most important properties of recycled aggregates from construction and demolition waste (CDW) used in road construction and maintenance, especially in unbound base and sub-base pavement layers. The National Laboratory of Civil Engineering (LNEC), in cooperation with the Technical University of Lisbon (IST), is carrying out a research project concerning the study of crushed concrete, which represents the majority of CDW generated by building and bridge construction in Portugal. Two origins of crushed concrete were analysed: material from laboratory crushing of cubic concrete specimens, used previously in compression strength tests and material from in situ crushing of CDW, obtained from a concrete building demolition site near Lisbon. The geometrical, physical and mechanical characterisation of materials in the laboratory was based on standard European tests established for natural aggregates: particle size distribution, shape index, flakiness index, Los Angeles fragmentation, micro-Deval wear, crushed and broken surfaces, sand equivalent, methylene blue and the compaction test. A chemical characterisation of all materials was also undertaken. The paper presents the laboratory test results and also discusses the main critical aspects related to the test procedures in light of the non-traditional nature of the CDW material. In 2006, LNEC published a guide, LNEC E 473, for the use of recycled aggregates in unbound base and sub-base pavement layers. Test results were compared with the requirements covered by this guide. Some main conclusions and recommendations derived from this analysis are presented in the paper.